Antimicrobial Susceptibility of Staphylococcus aureus Isolates from Chicken Meat and Ready to Eat Chicken Products in Jabalpur City - Thakur, Vijaya Singh; Gupta, Bhavana; Singh, R. V.; Nayak, Anju; Meravi, Sujata (International Journal of Livestock Research, 2019)
Staphylococcus aureus is Gram-positive, non-spore forming, non-motile commensal and opportunistic pathogen. In this study 66 S. aureus were obtained from170 samples of raw chicken meat and its ready-to-eat (RTE) chicken products. On In vitro antibiogram study of all the isolates of S. aureus against 16 different antimicrobials revealed S. aureus isolates showed resistance to tetracyline (67.6%), lincomycin (51.5%), erythromycin (48.4%) and ceftazidime (43.9%) and isolates were sensitivity to vancomycin (95.4%), ceftriaxone (92.4%), cefalexin (87.8%) and amoxicillin (83.3%). MAR (Multiple antibiotic resistance) index of various isolates indicates an overall range from 0.06-0.56 where in raw chicken meat and ready to eat (RTE) chicken products range varies from 0.06 to 0.56 and 0.06-0.37, respectively. Maximum isolates of S. aureus were resistant to one (25 isolates, MAR index 0.1) followed by resistance to 3 antibiotics (19 isolates, MAR index 0.3), resistance to 2 antibiotics (11 isolates, MAR index 0.2). In conclusion, the study revealed that the chicken meat and meat products in the study area were contaminated with S. aureus which indicates poor hygienic practices in slaughter house and retail outlets, further antibiotic resistant strains in raw chicken meat and especially ready-to-eat (RTE) chicken products are indicative of safety risk at consumer level.